New synonymies among species of Nitornus (Hemiptera: Heteroptera: Reduviidae) - Gil-Santana, Hélcio R. (Zootaxa, 2016)
Based on examination of types and additional specimens, the following new synonymies are proposed in the genus Nitornus Stål, 1859 (Hemiptera: Heteroptera: Reduviidae: Stenopodainae): Nitornus lobulatus Stål, 1859 = Nitornus monrosi (Wygodzinsky, 1959), syn. nov. = Nitornus barberi Froeschner, 1999, syn. nov.; and Nitornus parkoi (Costa Lima & Campos Seabra, 1945) = Nitornus seabrai (Prosen & Martínez, 1958), syn. nov. These synonymies result in Nitornus having only two valid species. Comments on morphological variations and the male genitalia of the species studied here are provided.